HUBUNGAN KEBIASAAN SARAPAN, POLA KONSUMSI FAST FOOD DENGAN STATUS GIZI REMAJA SMAN 1 TAMPAKSIRING - I Komang Bagus Saniartha; I Komang Agusjaya Mataram; I Made Suarjana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
The central obesity prevalence in Bali is 36% higher than the national prevalence in 2018. The highest prevalence of central obesity at the center of Tampaksiring with 28.87% in Gianyar. This research aims to determine the relationship between breakfast habits and fast food consumption patterns and quantity with the adolescent nutritional status in State High School 1 Tampaksiring, Gianyar regency. The type of observational research with cross-sectional design with a population number of 597 people and a sample amount of 65 people. Breakfast habits areobtained with questionnaires. Fast food consumption pattern obtained by interview method with form SQ-FFQ and form Recall 1x24 hours. Adolescent nutritional status data is determined by referring to the Z-score by doing height measurement and weighing weight. Further collected Data is processed using computer software to determine whether there is a relationship between variables. Samples have good breakfast habits with a score of 80 (20%). Samples consume fast food type that has a type of less or 12 types of fast food (66.2%). Samples often consume fast food with a frequency of 3-6x/week (38.5%). Sample with fast food amount with high consumption fast food day (80%). Samples have a normal adolescent nutritional status (83.08%). Based on the results of data analysis using a statistical test the Pearson correlation is known that there is no significant relationship (r=0,104, p=0,408) between breakfast habits and adolescent nutritional status. There is no significant relationship (r= 0,041, p=0,745) between the consumption patterns of fast food and the adolescent nutritional status. The conclusion of the research is no relationship between breakfast habits and adolescent nutritional status and than no relationship between the fast food consumption pattern and the adolescent nutritional status. Keywords: Adolescent Nutritional Status , Breakfast Habits, Consumption Patterns Fast Food